The Probability of Stroke Based on Clinical Decision Support System (CDSS) using the Framingham Risk Score Method in Hospital - Suryana, Arinda Lironika; Pratama, Mudafiq Riyan; Alfiansyah, Gamasiano (Puslitbang Sinergis Asa Professional, 2023)
Stroke is the main cause of death in Indonesia. Identification of stroke risk factors can use the Clinical Decision Support System (CDSS). Researchers have designed and developed a CDSS using the Framingham Risk Score (FRS) method to identify stroke in patients. The study aims to identify stroke risk factors using CDSS with the Framingham Risk Score method in dr Soebandi Hospital.This research was an analytic observational study using secondary data from medical record documents of neurology patients. . The sampling technique used was incidental sampling that met the inclusion criteria and exclusion criteria. The inclusion criteria used in selecting medical records were medical records that had complete data regarding gender, age, systolic blood pressure, total cholesterol, HDL, smoking behavior, history of diabetes mellitus, and the patient's stroke incidence thus obtaining 14 patient medical records.. Data were analyzed using the FRS method. Based on the research results, it can be concluded that there were 8 patients with high risk and 6 patients with low risk. However, further research needs to be carried out on the relationship between variables so that they can contribute in more detail to efforts to reduce the prevalence of stroke in society.